Reading Attitudes, Preferences, and Well-Being of Postgraduate Students: Case Study of a Nigerian Higher Education Institution - Nwagwu, Williams; Uloaku Maxwell, Fransisca (Journal of Information and Knowledge, 2026)
This study was carried out to investigate the well-being associated with the reading preferences and attitudes of postgraduate students at the University of Ibadan, Nigeria. Bronfenbrenner’s Ecological Systems Theory and Sweller’s Cognitive Load theory provided the framework for this study. Data was collected from 359 postgraduate students using a questionnaire and an interview guide. Students showed a strong preference for reading, with enjoyment of reading scoring a mean of 4.01 (SD = 0.96) and reading’s importance to daily life at 4.14 (SD = 0.86). Preferences leaned towards academic/ educational books (Mean = 4.09, SD = 1.02) and motivational books (Mean = 3.41, SD = 1.16). Notably, 78.7% agreed that reading positively affects their well-being and mental health (Mean = 4.06, SD = 0.89). The study found a very weak positive correlation (R = 0.137) between attitude and well-being, with attitude explaining only 1.9% of the variance (R² = 0.019). The regression model was statistically significant (F = 5.798, p = 0.017). Reading did not significantly increase stress for most students, and physical symptoms like headaches or insomnia post-reading are uncommon. Reading did not typically lead to negative emotions, with low scores on feelings of sadness or hopelessness. Instead, reading contributed to a sense of purpose and emotional coping, with many students feeling it enhanced their understanding and management of emotions. 1.